Broadband CPW—fed star shape patch antenna backed by rectangular ring ground plane. Issue 10 (27th July 2016) - Deshmukh, Amit A.; Agrawal, Sudesh R.; Lele, Kshitij A.; Ray, K. P.
ABSTRACT: A novel design of broadband CPW‐fed star shape patch antenna backed by rectangular ring ground plane is proposed. The star shape patch realized by combining two triangular shape patches, yields bandwidth of more than 5 GHz (>130%). Over the bandwidth, proposed antenna shows broadside radiation pattern with a peak gain of 3 dBi. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2443–2450, 2016